Isokinetic profile of subjects with the ruptured anterior cruciated ligament - Drapšin, Miodrag P; Lukač, Damir; Rašović, Predrag; Drid, Patrik; Klašnja, Aleksandar; Lalić, Ivan (Vojnosanitetski pregled, 2017)
Background/Aim. All changes in the knee that appear after anterior cruciate ligament (ACL) lesion lead to difficulties in walking, running, jumping especially during sudden changes of the line of movement. This significantly impairs quality of life of these subjects and leads to decrease in physical activity. Knee injuries make 5% of all most severe acute sport injuries. The aim of the study was to determine strength of the thigh muscles in persons with unilateral rupture of the ACL and to evaluate potential bilateral differences between healthy and injured leg. Methods. This study involved 114 male athletes of different sport specialities with the clinical diagnosis of ACL rupture. Each subject had unilateral ACL rupture and the other leg was actually the control for this research. An isokinetic device was used to evaluate the muscle strength of thigh muscles. Testing was performed for two testing speeds, 60º/s and 180º/s. Results. Data analysis showed a statistically significant difference (p < 0.01) between the ACL and the healthy leg in the following parameters: peak torque for thigh extensors (Ptrq_E), angle to peak torque during extension (Ang_E), power of extension (Pow_E) and work during extension (Work_E). Analysing hamstrings to quadriceps (H/Q) ratio we found the unilateral disbalance of thigh muscle strength in ACL leg. Conclusion. A high level of validity makes isokinetic dynamometry the method for evaluation of thigh muscles strength and leaves this field of research open for new studies in order to improve both diagnostic and rehabilitation of patients with the insufficient ACL.